PERENCANAAN ARSITEKTUR ENTERPRISE MENGGUNAKAN EAP DENGAN ZACHMAN FRAMEWORK (Studi Kasus : CV BIENSI FESYENINDO) - Anjas Tryana (Jurnal Accounting Information System (AIMS), 2019)
With the development of technology today, it is very important for every company to plan and develop a system to support business processes in each company. Achieving the goals of an enterprise faces challenges and changes that require strategies for effective measures and efficient use of resources. One important and increasingly widely used strategy is the use and improvement of information system support for the enterprise. This plan can utilize enterprise architecture planning methodology that produces data architecture, application architecture, technology architecture, and the direction of its implementation plan for the enterprise.CV Biensi Fesyenindo is engaged in retail garment, with branches throughout Indonesia, covering the areas of Kalimantan, Sulawesai, NTB, NTT, Bali, Java and Sumatra. In their daily activities, they carry out production to distribution processes to meet market and employee needs.The enterprise architecture model used in this study is by using Enterprise Architecture Planning (EAP). EAP is a process of defining enterprise architecture that focuses on data architecture, applications and technology in supporting business and plans to implement the architecture, where the EAP method has several stages, starting from planning in planning, business modeling , Current System and Technology (Current System & Technology), Data Architecture (Data Architecture), Application Architecture (Applications Architecture), Technology Architecture (Technology Architecture), Implementation Plans (Implementation Plans).The results of this study are recommendations for information systems for Fesyenindo Biensi CV in the form of enterprise architecture planing blue print planning that is successful in defining 5 main business processes, which consist of application architecture data architecture and for technological architecture to produce technology architecture proposals divided into 5 chapters 110 pages .